The Effect of the Introduction of the Euro on Asymmetric Stock Market Returns Volatility Across the Euro-Zone - Simon Moorhead; Robert Brooks (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The aim of this paper is to examine the effect that the increase in integration, culminating in the introduction of the euro currency, had on returns volatility across the different members of the currency union. We analyse the twelve countries that adopted the euro in January 2002, over the sample period July 1990 to December 2006. Volatility is measured across each of four sub-periods for TARCH and APARCH models because of their ability to account for asymmetries in the data. We find that overall there is a distinct change in the dynamics of asymmetric volatility across the various stages in the introduction of the euro. The first sub-period shows evidence of asymmetric volatility in only a few countries. The relaxation of the rejection criterion in the second sub-period allows for an increase in the number of countries where asymmetric volatility is present and in the third and fourth sub-periods almost all of the countries analysed display asymmetric volatility.
Keywords: G15; 650; Euro Introduction; Stock Return Volatility; Asymmetry; European Markets